PELATIHAN BUDIDAYA TUMBUHAN ANTI NYAMUK UNTUK PENCEGAHAN KASUS DEMAM BERDARAH DENGUE DI KELURAHAN SIANTAN TENGAH, PONTIANAK - Iskandar Arfan; Peronela Peronela (Jurnal Buletin Al-Ribaath, 2016)
Dengue fever si major concern in Pontianak because of the high number of cases. In 2012 to 2014,  dengue Ever incidents in Pontianak showed fluctuating trend where in 2012 (IR 23.1), 2013 (IR 17:06), and increased dramatically in 2014 to 57.07 per 100,000 population. Mortality rate (CFR) for dengue fever in 2014 was 2.03% and exceeded national rate. Various efforts have been made by the community to eradicate the mosquito-borne dengue disease. The use of mosquito repellant plant is a cheap and environmentally friendly alternative that allows people to avoid mosquito bites because it does not leave pungent odor and can cause poisoning such as anti-mosquito drugs. Mosquito repellent plants sosialization activities was held in the meeting hall PKK Siantan Tengah Kelurahan, Pontianak on Tuesday, Sept. 8, 2015. The results of questionnaires showed that socialization repellant mosquito plant cultivation wass very interesting and useful knowledge to prevent dengue fever. It was expected to target in particular the PKK cadres can disseminate to the entire community related knowledge, cultivation and application of mosquito repellent plants that has been socialized, the relevant agencies such as health centers and villages in order to always support and promote programs cultivation of plant mosquito is by providing assistance in the form of growing media and soil for the development of medicinal plant seeds center.Key words: socialization, mosquito repelllant plants, dengue fever